Specific Diagnosis of Spontaneous Mediastinal Emphysema - M. D. Romanov; E. M. Kireeva; T. M. Levina (Туберкулез и болезни лёгких)
The article describes a clinical observation of an 18-year-old patient suffering from bronchial asthma complicated by mediastinal emphysema which developed during a coughing attack. It demonstrates the possibilities of computed tomography in the complex diagnosis of spontaneous mediastinal emphysema.